Emotional Substrates in Neuroticism: The Reactions to Arousal-evoking Stimuli of Various Strengths - Yusoff, N; Reza, F; Anuar, NN; Ahmad, R (IBN SINA Trust, 2024)
Objective: Neuroticism is a medical condition associated with negative affect and is considered to predispose one to mental disorders. This study examined the effects of arousal-evoking stimuli of various strengths on the severity of neuroticism. Materials and Methods: In the Event Related Potential (ERP)/electroencephalograph (EEG) recording session that was held at the Clinical Neuroscience Laboratory at a local hospital, Electroencephalogram was recorded in 58 participants (N=29 for moderate neuroticism and 29 for mild neuroticism) after they were screened for the severity of the neurotic trait. Universal emotional pictures were chosen randomly from the International Affective Picture System (IAPS) and were used as visual stimuli in the experiment. Visual stimuli were divided into three categories (high, moderate, low) based on the IAPS normative mean values of arousal. Results: The significant interaction effect of P300 latency between neuroticism and arousal strength was found in the mid-frontal region. Meanwhile, independent of neuroticism, the main effects of arousal strength of the P300 (amplitude and latency) and N200 (latency) were observed in the mid-central region. Conclusion: There is a significant interaction between the severity of neuroticism and the emotional arousal strength, thus, points to the implication of the emotion process in the brain rewards system especially among individuals with neuroticism.